Antecedents of organizational citizenship behaviour and mediating role of affective commitment among support staff of research universities in Malaysia - Mohamed Idrus, Rosafizah (2019)
Presently, there is a greater emphasis on exploring positive human resource strengths to address the workplace challenges in order to amplify organizational performance. Resilience, self-efficacy, organizational support and affective commitment are part of personal and work-related factors that contribute to positive human resource strengths that relates to desired attitudes, behaviors, and performance such as organizational citizenship behavior (OCB). OCB is a unique aspect of employee's behaviors in the workplace which is regarded as one of the important requirements and prerequisite for organizational effectiveness, efficacy, productivity and performance. OCB is crucially needed in every organization, including in higher education setting. For this reason, the purpose of this study is to examine the underlying relationship between resilience, self-efficacy, organizational support and affective commitment with two dimensions of OCB and evaluated as to whether the behaviors are inclined towards individuals (OCBI) or organization (OCBO). This study adopted quantitative research paradigm employing correlational research methodology. The unit of analysis is the individual support staff. The sample comprised of 487 respondents consists of support staff from five Research Universities (RUs) in Malaysia. mM SPSS version 25 Statistical Package and the Structural Equation Modeling (SEM) with Analysis of Moment Structures (AMOS) was used to analyze the data. The finding indicated that these staff possess high level of resilience, self-efficacy, affective commitment and OCBO whilst moderate to high level of organizational support and OCBI. The result also showed that all constructs were related positively to OCBI whereby, only three constructs namely resilience, self-efficacy and affective commitment were positively related to OCBO. The result has shown that affective commitment mediated the relationship between self-efficacy and organizational support with OCBI and OCBO but then it was not an underlying factor to explain the relationship between resilience with OCBI and OCBO. Results from this study provided empirical evidence that relational theories (Social Cognitive Theory, Social Exchange Theory, Resilience Theory and Self- Efficacy Theory) were fit thereby applicable in the explanation of significant contribution of personal and work-related factors that have great influence to the willingness of the staff extending extra effort voluntarily beyond their official job description which eventually benefit the RUs in the long run. These respective staffs can be assisted to reach their ultimate potentials and continue in contributing to the attainments of the respective RUs by providing the proper ambience and support thus, ensuring optimization of human resources in the RUs practiced. Consequently, it is essential for the respective RUs to offer the correct environment and equipped with ample opportunities in encouraging growth and development of their staff. This will underpin the Human Resource Development (HRD) in managing the ready and potential staffs strategically. As these are means and ways to motivate, improve and improvise the forte and strength of each staff thru nurturing their positive attitudes that covers personal to workrelated aspects (OCB, resilience, self-efficacy, organizational supports and affective commitments) and enable the RUs to steer and propel the university with positive organizational implications and outcomes in the new global economy in this era.